Study Of User Behavior Towards Adoption Of Kuassa Digital Audio Technology: UTAUT2 Approach - Alam Pratiwi, Restu; Candra Astuti, Novika (International Journal of Science, Technology & Management, 2025)
This research aims to analyze the factors influencing the intention to adopt Kuassa's products—an Indonesian digital audio software development company—by domestic consumers, using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. Although Kuassa has achieved success in the international market, its market share in Indonesia remains very low, at less than 1%. This research uses a quantitative approach with a survey method involving 133 respondents, consisting of professional musicians, audio engineers, bedroom musicians, music educators, and fans of digital music production in Indonesia. Data analysis was conducted using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The research results show that four variables in the UTAUT2 model, namely price value, facilitating conditions, performance expectancy, and hedonic motivation, significantly influence the intention to adopt Kuassa products. On the other hand, effort expectancy and social influence do not show a significant impact. These findings indicate that perceptions of product value, availability of technical support, performance expectations, and aspects of enjoyment play an important role in driving the adoption of digital audio technology in Indonesia. This research provides practical implications for Kuassa in formulating marketing strategies, market education, and product development that better align with the needs and preferences of the local market.